Exploring farmers’ practices and perceptions of groundwater extraction as a key component of integrated water management in the Dayet Aoua watershed, Middle Atlas, Morocco - El Idrissi Mohammed Chrif; Saber Er-Riyahi; Mazi Mohamed El (Environmental & Socio-economic Studies, 2025)
In the Middle Atlas region of Morocco, the expansion of irrigated agriculture has led to escalating pressure on groundwater resources, particularly in the Dayet Aoua watersheda zone experiencing both hydrological vulnerability and socio-economic transformation. This study explored how well-owning farmers perceive and manage groundwater in a context marked by increasing resource scarcity, institutional gaps, and climate variability. Based on a structured survey of 80 farmers and supported by statistical analysis, including chi-square tests, the research examined the technical characteristics of wells, water use practices, and farmers’ awareness of groundwater over-exploitation. The findings reveal a significant disconnect between widespread recognition of groundwater as a limited resource (over 90%) and the persistence of unsustainable extraction behaviours, driven by economic dependence, energy subsidies, and the absence of regulatory enforcement. Furthermore, the study identifies socio-technical inequalities in access to groundwater infrastructure and highlights the influence of infrastructure type on farmers' perceptions. The results underscore the need for integrated, participatory groundwater governance that accounts for local knowledge, institutional shortcomings, and differentiated user capacities. By linking perceptions to practice, this study contributes to the broader discourse on sustainable water resource management in semi-arid agricultural systems.